Omega-3 and omega-6 fatty acids as food supplements from marine fishes of Tuba Island, Langkawi, Malaysia - Jaswir, Irwandi; Saeed Mirghaini, Mohamed Elwathig; Mohd. Salleh, Hamzah; Osman, Farida (2009)
Fish lipids are well known to be rich in long chain polyunsaturated fatty acid (PUFA), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). These fatty acids play a vital role in human nutrition, disease preventaion, and health promotion. In addition, DHA and arachidonic acid (AA), an PUFA, are structural components....